2020
DOI: 10.3390/molecules25184074
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Physicochemical, Rheological, and Antibacterial Properties of Chitosan Extracted from Antarctic krill: A Comparative Study

Abstract: In this work, physicochemical, rheological, and antibacterial properties of chitosan (CS) extracted from white shrimp (WS), giant river prawn (GP), and Antarctic krill (AK) were investigated. The results demonstrated that molecular weight (MW) of commercial chitosan (CCS), WSCS, GPCS, and AKCS were 1175.8, 2130.4, 1293.3, and 1109.3 kDa with the degree of deacetylation (DDA) of 73.5, 74.1, 82.1, and 75.9%, respectively. Fourier transform infrared (FT-IR), X-ray diffraction (XRD), differential scanning calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…According to the findings of [19], the variation in chitosan yield may have been due to excessive depolymerization of the chitosan polymer, and loss of the sample due to excessive removal of acetyl groups during deacetylation. The chitosan yield obtained was also comparable to other sources, such as cockroaches, shrimp, Musca domestica, and krill [33][34][35].…”
Section: Chitin Yield From the Pupal Exuviae Of The Black Soldier Flysupporting
confidence: 66%
“…According to the findings of [19], the variation in chitosan yield may have been due to excessive depolymerization of the chitosan polymer, and loss of the sample due to excessive removal of acetyl groups during deacetylation. The chitosan yield obtained was also comparable to other sources, such as cockroaches, shrimp, Musca domestica, and krill [33][34][35].…”
Section: Chitin Yield From the Pupal Exuviae Of The Black Soldier Flysupporting
confidence: 66%
“…The DDAs determined here by this method (DAFR) were significantly lower at 66% (EA) and 74% (NMR). Yuan et al 14 reported a DDA of only 75% for chitosan produced from Antarctic krill chitin.…”
Section: Resultsmentioning
confidence: 99%
“…The determined molecular weights are relatively low compared to values published by other authors applying viscosimetry for the determination. For example, Yuan et al 14 determined 1110 kDa for a chitosan from Antarctic krill. In some cases, however, lower polymer lengths were determined, such as 157 kDa by Wu et al 58 The concentration of sodium hydroxide solution, temperature, and incubation time can generally have a negative influence on the molecular weight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional chemical methods to extract chitin from crustacean shell wastes involve three steps: demineralisation, deproteinisation and decolourisation. In the first step, crustacean shells are washed, dried, and grounded to smaller sizes [ 42 ]. In order to remove mineral constituents, mainly calcium carbonate, the powdered raw material is treated with dilute hydrochloric acid followed by the precipitation of calcium chloride.…”
Section: Chitosanmentioning
confidence: 99%